Pulses for nutrition in India: Changing patterns from farm to fork - Roy, Devesh; Joshi, Pramod Kumar; Chandra, Raj (International Food Policy Research Institute, 2017)
India, a country with high concentrations of poor and malnourished people, long promoted a cereal-centric diet composed of subsidized staple commodities such as rice and wheat to feed its population of more than a billion. Today, however, dietary patterns are changing. Policy makers, researchers, and health activists are looking for ways to fight hunger and malnutrition in the country. As they shift their focus from calorie intake to nutrition, neglected foods such as pulses (the dried, edible seeds of legumes) are gaining attention. Pulses for Nutrition in India: Changing Patterns from Farm to Fork explores the numerous benefits of a diet that incorporates pulses. Pulses, including pigeonpeas, lentils, and chickpeas, are less expensive than meat and are excellent sources of protein. In India, people consume pulses and other legumes for protein intake. Pulses also benefit the ecosystem. Among protein-rich foods, pulses have the lowest carbon and water footprints. Pulses also improve soil health by naturally balancing atmospheric nitrogen in the soil; thus, growing pulses reduces the need for nitrogenous fertilizer. Pulses for Nutrition in India: Changing Patterns from Farm to Fork looks at the country’s pulses sector in light of agricultural systems, climate change, irrigation design, and how policies (including the Green Revolution) have evolved over time. To understand how pulses can help fulfill the objectives of India’s food policies, experts explore the role that pulse production plays in global trade; the changing demand for pulses in India since the 1960s; the possibility of improving pulse yields with better technology to compete with cereals; and the long-term health benefits of greater reliance on pulses. The analyses in Pulses for Nutrition in India: Changing Patterns from Farm to Fork contribute to the emerging literature on pulses and will aid policy makers in finding ways to feed and nourish a growing population.